The Science of Solar System Ices - Gudipati, Murthy S.; Castillo-Rogez, Julie; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The Science of Solar System Ices The role of laboratory research and simulations in advancing our understanding of solar system ices (including satellites, KBOs, comets, and giant planets) is becoming increasingly important. Understanding ice surface radiation processing, particle and radiation penetration depths, surface and subsurface chemistry, morphology, phases, density, conductivity, etc., are only a few examples of the inventory of issues that are being addressed by Earth-based laboratory research. As a response to the growing need for cross-disciplinary dialog and communication in the planetary ices science community, this book aims to foster focused collaborations among the observational, modeling, and laboratory research communities. The book is a compilation of articles from experts in ices: experimentalists, modelers, and observers (ground-based telescopes and space missions). Most of the contributors featured in this book are renowned experts in their respective fields. Many of these scientists have also participated in the book entitled Solar Systems Ices (Kluwer Academic Publishers, 1998) in the Astrophysics and Space Science Library Series.
Foreword -- Preface -- Acknowledgements -- Part I - Optical Remote Sensing of Planetary Ices -- Chapter 1: Observed Ices in the Solar System -- Chapter 2: Photometric Properties of Solar System Ices -- Chapter 3: Ultraviolet Properties of Planetary Ices -- Chapter 4: The Ices on Transneptunain Objects and Centaurs -- Part II: Ice Physical Properties and Planetary Applications -- Chapter 5: First-Principles Calculations of Physical Properties of Planetary Ices -- Chapter 6: Frictional Sliding of Cold Ice: A Fundamental Process Underlying Tectonic Activity Within Icy Satellites -- Chapter 7: Planetary Ices Attenuation Properties -- Chapter 8: Deformation Behavior of Ice in Polar Ice Sheets -- Chapter 9: Cratering in Icy Bodies -- Chapter 10: Geology of Icy Bodies -- Part III - Volatiles in Ices -- Chapter 11: Amorphous and Crystalline H2O-Ice -- Chapter 12: Clathrate Hydrates: Implications for Exchange Processes in the Outer Solar System -- Chapter 13: Cometary Ices -- Chapter 14: Gas Trapping in Ice and Its Release Upon Warming -- Part IV: Surface Ice Chemistry -- Chapter 15: Chemistry in Ices - From Fundamentals to Planetary Applications -- Chapter 16: Radiation Effects in Water ice in the Outer Solar System -- Chapter 17: Sputtering of Ices -- Chapter 18: Photochemistry in Terrestrial Ices -- Index.
Keywords: Physics; Space sciences; Solid state physics; Spectroscopy; Microscopy; Materials science; Physics; Extraterrestrial Physics, Space Sciences; Characterization and Evaluation of Materials; Solid State Physics; Spectroscopy and Microscopy; Electronic books